EFFECT OF PROBLEM BASED LEARNING ON METACOGNITIVE AND HIGHER THINKING ABILITY IN HIGH SCHOOL BIOLOGY: STUDY OF LITERATURE - Ihza Sania Risti; Hani Irawati (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Students are required to be capable of 21st Century Skills in biology learning. One of the demands is metacognitive ability and higher order thinking skills. This study aimed to determine the effect of Problem Based Learning (PBL) on metacognitive abilities and high-order thinking skills of high school students in biology learning, by studying literature with narrative review. The data is presented in a table listing scientific articles which were analyzed descriptively into research data. Based on the analysis, it is known that PBL has an effect on students' metacognitive and higher order thinking abilities. With PBL, students are helped to improve their metacognitive abilities so that they can think to solve problems. The stages in PBL are related to aspects of higher order thinking skills. This shows that PBL affects students' metacognitive and higher order thinking abilities.